A Prognostic Model for Colon Cancer Patients Based on Eight Signature Autophagy Genes - Xu, Jiasheng; Dai, Siqi; Yuan, Ying; Xiao, Qian; Ding, Kefeng (Frontiers in Cell and Developmental Biology, 2020)
Objective:To screen key autophagy genes in colon cancer and construct an autophagy gene model to predict the prognosis of patients with colon cancer. Methods:The colon cancer data are from theTCGA, data chip of GSE17536 as the validation set. The differential genes of the training set were obtained for enrichment and protein network. Acquire autophagy genes from Human Autophagy Database www.autophagy.lu/project.html. Autophagy genes in differentially expressed genes were extracted using R-packages limma.CIBERSORT calculates the infiltration of immune cells in the samples and study the relationship between high and low risk groups and immune checkpoints. Results:976 differentially expressed genes were screened from training set, including 568 up-regulated genes and 408 down regulated genes. These differentially expressed genes were mainly involved:the regulation of membrane potential,neuroactive ligand-receptor interaction. We identified eight autophagy genes CTSD,ULK3,CDKN2A,NRG1,ATG4B,ULK1,DAPK1 and SERPINA1 as key prognostic genes.Nomogram assessment showed that the model had high reliability for predicting the survival of patients with colon cancer in the 1,3,5 year. In the high-risk group,the infiltration degrees of 9 types of immune cells are different.Immunological checkpoint correlation results showed that the expression levels of CTLA4, IDO1, LAG3, PDL1 and TIGIT increased in high-risk groups. Conclusion:The prognosis prediction model based on autophagy gene has a good evaluation effect on the prognosis of colon cancer patients. 8 key autophagy genes can be used as prognostic markers for colon cancer.